The effect of caffeine on maximal oxygen uptake and vertical jump performance in male basketball players - Tucker, M. A.; Hargreaves, J. M.; Clarke, J. C.; Dale, D. L.; Blackwell, G. J. (The Journal of Strength and Conditioning Research, 2013)
This study investigated whether performance enhancement from caffeine described by other researchers transfers to male basketball players. The effects of caffeine ingestion were studied in a maximal-effort test on a treadmill that was followed by a vertical-jump test. Five elite-level male basketball players completed a graded treadmill test that measured maximal oxygen uptake, blood lactate profiles, respiratory exchange ratio, and rating of perceived exertion at each 3-minute stage. After a 15-minute warm-down, the subjects performed 10 vertical rebound jumps. Each subject completed the test twice—once with a 3 mg/kg of body weight dose of caffeine and once with a placebo, with the dosage administered 60 minutes before commencement of exercise. The test was thus administered according to a double-blind protocol. No substantial trends were found between caffeine and control trials, regardless of trial order. The study showed that the specified dosage had negligible effects on the players' power and endurance performance and had no efficacy as an ergogenic aid for male basketball players.